KAJIAN MANAJEMEN PRODUKSI PEMBERITAAN PSO BIDANG PERS OLEH LKBN ANTARA - Primayanti, Primayanti (Jurnal Visi Komunikasi, 2015)
Based on Government Regulation No. 40 Year 2007 on Perum ANTARA do fund public services (public service obligation / PSO) in the field of government information. ANTARA position is also very strategic in the middle of the fight-laden media industry interests. Also, the need to get in the news media with the retail product line strategy while maintaining the main products for the media.Results of this study showed that the press area of public service obligations (PSO-Field Press) includes a number of products and services that news text, photo news, and TV news. In line with government policies and programs, also set a number of themes that frame the products and services fields PSO Press.PSO and Field Releases can be interpreted as the government's efforts to maintain control and domination of the media life, given the strategic function of political economy of media. A contradiction was born. On the one hand, the government wants to adopt the principles of the liberal press, on the other hand maintain government policies in the media sector as opposed to the spirit of libertarianism. Berdasarkan Peraturan Pemerintah Nomor 40 Tahun 2007 tentang Perum LKBN ANTARA dilakukan dana pelayanan umum (public service obligation/PSO) di bidang informasi dari pemerintah. Posisi LKBN ANTARA juga sangat strategis di tengah pertarungan industri media yang sarat kepentingan. Juga, perlunya kantor berita masuk media ritel dengan strategi lini produk dengan tetap mempertahankan produk utama untuk media.Hasil penelitian ini menujukkan bahwa kewajiban pelayanan umum bidang pers (PSO-Bidang Pers) tersebut mencakup sejumlah produk dan layanan yaitu berita teks, berita foto, dan berita TV. Agar sejalan dengan program dan kebijakan pemerintah, ditetapkan pula sejumlah tema yang membingkai produk dan layanan PSO Bidang Pers.PSO Bidang Pers dapat dimaknai sebagai upaya pemerintah yang ingin mempertahankan kontrol dan dominasinya terhadap kehidupan media, mengingat begitu strategisnya fungsi ekonomi-politik media. Sebuah kontradiksi pun lahir. Di satu sisi, pemerintah ingin mengadopsi prinsip-prinsip pers liberal, di sisi lain pemerintah mempertahankan kebijakan-kebijakan di sektor media yang bertentangan dengan semangat libertarianisme.